Neurophysiological Insights into Network Decoding of Working Memory: An Analysis of Human Brain Electrophysiological Signals - Mahdieh Tahanejad; Zahra Bahmani (Frontiers in Biomedical Technologies)
Purpose: The human brain is comprised of distinct regions, each contributing uniquely to behavioral control. The execution of even basic tasks necessitates synchronized activities among multiple brain regions. Fundamental cognitive functions hinge on the capacity to retain and flexibly manipulate information, a key role ascribed to Working Memory (WM). This study seeks to enhance our understanding of the neural mechanisms underlying WM and elucidate the coordinated neural activities spanning various brain regions.